(untitled) (Swiss Medical Weekly, 2017)
With a hepatitis B prevalence of 0.3%, Switzerland is a country with low endemicity. Unlike most other countries, Switzerland’s recommendation for vaccination against hepatitis B has since 1998 focused on adolescents aged 11 to 15 years rather than on infants, in addition to risk groups since 1982. This paper describes the evolution of the incidence of acute hepatitis B virus (HBV) infection and newly reported chronic cases in Switzerland, as well as their epidemiological features, in order to discuss the implications for the control of hepatitis B through vaccination. Data from mandatory notifications by physicians and laboratories between 1988 and 2015 were analysed for acute and chronic HBV infection. Crude and stratified incidence and notification rates (IR, NR), and incidence and notification rate ratios (NRR, IRR) by year were calculated by means of a Poisson regression. Acute HBV incidence peaked in 1992 at 7.5 cases per 100 000 population and subsequently declined by 11% annually (IRR 0.89, p <0.001) to the lowest rate of 0.4/100 000 in 2015. The decrease in incidence accelerated after the introduction of vaccination for adolescents (IRR 0.93, p <0.001 vs 0.91, p <0.001), and was more pronounced in the targeted age groups (IRR 0.90, p <0.001 vs 0.84, p <0.001 for age 15–19 years and IRR 0.92, p <0.001 vs 0.83, p <0.001 for age 20–24). The use of injectable drugs as an assumed source of exposure decreased from 58.1% to 1.9% of all exposures between 1988–1991 and 2012–2015, while sexual contact with an infected person increased from 10.3% to 67.9%. The NR of chronic cases increased until 1995, then stabilised at around 15/100 000. A growing majority of the chronic cases originated abroad (58.4% in 1988–1991 and 82.2% in 2012–2015), and the NR was significantly higher for foreigners than for Swiss nationals (NRR 7.92, p <0.001), especially when compared with the IRR of 1.55 (p <0.001) for acute cases. The introduction of universal vaccination of adolescents combined with vaccination of risk groups and other nonvaccine-related measures has brought acute HBV infection under control in Switzerland. However, the rate of new notifications of chronic HBV infection has remained stable, largely as a result of the immigration of people chronically infected prior to arrival. The burden of disease is thus likely to increase, requiring the strengthening of secondary prevention of chronic HBV infection, in addition to renewed efforts to vaccinate people and their families originating from countries with high endemicity, and persons who frequently change sexual partners.